Effect of Working Capital Turnover on Economic Profitability at PT. Vale Indonesia, Tbk - Rati Pundissing; Chrismesi Pagiu (Institute of Computer Science (IOCS), 2022)
This study aims to provide empirical evidence regarding whether or not there is an influence or relationship between working capital turnover and economic profitability at PT. Vale Indonesia, Tbk. The type of research used is quantitative research with data analysis techniques that become the research reference, namely based on the financial ratio measurement scale and statistical analysis using SPSS version 16. The results show that there is a significant effect of working capital turnover on economic profitability as indicated by the t-test which is significant at 0.003 which is less than 0.05 or sig 0.003 < 0.05. t count > t table that is 5.506 > 2.571 then H 0 is rejected, and Ha is accepted. The correlation coefficient is 0.927, meaning that the relationship between working capital turnover (X) and economic profitability (Y) is very strong, which is in the range of 0.80 – 1,000 based on Pearson's provisions. While the value of the coefficient of determination (R 2) is 0.858. This means that working capital turnover (X) affects economic profitability (Y) by 85.8 % and the remaining 14.2% is influenced by other variables not included in the study.